The Effect of Dimethyl Sulfoxide on the Microtensile Bond Strength of Universal Adhesives to Dentin - Zahra Dadvar; Mohammad Esmaeel Ebrahimi Chaharom; Soodabeh Kimyai; Mahmoud Bahari; Mehdi Daneshpooy (Tehran University of Medical Sciences, 2024)
Objectives: The goal of this investigation was to see how a dentin pretreatment with 5% DMSO affected the microtensile bond strength (μTBS) of universal adhesives. Materials and Methods: In terms of adhesive kind and etching procedure, 32 healthy third human molars were randomly separated into eight groups. Three universal adhesives with etch-and-rinse and self-etch strategies (G-Premio Bond: GPB.ER/SE, All-Bond Universal: ABU.ER/SE, Prime & Bond Elect: PBE.ER/SE), one two-stage self-etch adhesive (Clearfil SE Bond: CSB), and one two-stage etch-and-rinse adhesive (Adper Single Bond 2: ASB) were employed in with and without DMSO modes (group/N=16). Dentin pretreatment was conducted with 50 μl of 5% DMSO, followed by the use of an adhesive. The μTBS of samples was tested. The influence of adhesive type and DMSO application on bond strength was evaluated using a two-way analysis of variance (ANOVA) (=0.05). Results: The dentin-adhesive μTBS was significantly affected by DMSO administration (P=0.003), type of adhesive (P=0.001), and the combination of DMSO application and type of adhesive (P=0.027). In the DMSO application mode, the average bond strength of universal adhesives with etch and rinse mode was significantly higher than in the non-application mode, but in the self-etch technique, there was no significant difference pattern between DMSO applications and non-application modes in terms of adhesive bond strength. Conclusion: The use of DMSO in an etch-and-rinse technique can dramatically enhance the universal adhesive-dentin μTBS and has promise benefits for clinicians in terms of enhancing dentin bond performance.